Determination of Regularities in the Development of Intermodal Hubs’ Planning Structure in «Smart» Cities - Vlasov Denis; Terekhova Anna (E3S Web of Conferences, 2019)
This article is an attempt to determine regularities in the development of transport and transfer hubs. One of the components of the “smart city” concept is the “smart transport”. The development of the transport system of a locality is one of the cornerstones for sustainable development of the urban territory, creating comfortable environment for human activities. The transport and transfer hub is the reference point of interaction between the urban environment and the transport infrastructure. When elaborating urban planning documentation for transfer hubs, special focus shall be made on the creation of comfortable and safe environment using the Transit Oriented Development (TOD) principles. At present, in Russia, the baseline document for territorial planning, which determines the limit parameters of the planned territory development, is the planning design. In Moscow and Moscow region, audacious transfer hub development programs have been adopted. Still, the regulatory and procedural framework for transfer hub planning is currently at the stage of elaboration. The goal of this study is to ascertain regularities between relevant and anticipated features of transfer hubs, based on approved hub plans in Moscow region. In particular, to reveal the dependence between the sizes of commercial areas making part of a hub, and the passenger traffic volume. The study uses the statistical method of regression analysis, which allows determining the function between dependent and independent variables. The model obtained can subsequently be used to calculate the limit parameters of the hub territory development, both at the stage of creating the hub development concept, and at the planning stage, to make well-grounded decisions as to limit parameters of the development.